Photocatalytic remediation of an organophosphorus pesticide using the composite SnO2/Fe2O3 with visible light irradiation - Almeida da Silva, Luciana; dos Santos Borges, Sheila; dos Santos Ramos, Luana Tássia (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
Pesticides are considered hazardous organic pollutants. It is estimated that about a third of the total mass of pesticides applied to the soil remains as a soil-bound residue in agricultural areas. Widely used worldwide as an insecticide and avicide, Fenthion (O, O-dimethyl-O-(4-methylmercapto)-3-methylphenylthio-phosphate) is a thioether organophosphorus pesticide detected as residue in several agricultural products (SANTOS et al., 2021). The development of methods and suitable materials to remove organic pollutants from water and other matrices has been a major concern among researchers. Photocatalysis is one type of advanced oxidative process (AOP) considered a green technique with the potential for eliminating toxic chemicals in the environment using sunlight. Herein, we evaluated the photocatalytic performance of the composite SnO2/Fe2O3 on fenthion degradation, which is non-toxic and responsive to visible light. The composite SnO2/Fe2O3 was synthesized from the Pechini method in a ratio SnO2:Fe2O3 of 3:1 and characterized by XRD, DRS, SEM, EDS, FT-IR, and ASAP. The photocatalytic reactions were performed under visible light irradiation (l > 420 nm) using 100 mg of photocatalyst, 100 mL of fenthion solution 30 mg L-1, at pH 4.0, 6.5 and 10, and hydrogen peroxide in different concentrations. The required adsorption time before irradiation was determined for each pH condition (Fig. 1a). HPLC with a DAD detector was used to monitor the decrease in fenthion concentration during irradiation. The condition that resulted in the highest fenthion photodegradation was at pH 4 with 200 mg L-1 hydrogen peroxide (Fig. 1b and c). This condition led to 91% degradation of fenthion in 4 hours, with an apparent rate constant of 1.05 x 10-2 min-1. This value is much larger than that obtained through photolysis (5.7 x 10-3) and catalysis (6,9 x 10-3) experiments (Fig 1d). Further, our results are also much higher than those already published, such as fenthion degradation under UVA A (5.5× 10-3 min-1) and UVB B (9.9×10-3 min-1) irradiation and under natural sunlight (3.3 × 10-4 min-1) (SANTOS et al., 2021; SAKELLARIDES et al., 2003), which demonstrates the potential of the composite SnO2/Fe2O3 in fenthion remediation under sunlight irradiation.